2016
DOI: 10.9721/kjfst.2016.48.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Rice Volatile Compounds under Different Milling Degrees and Storage Time Using an Electronic Nose

Abstract: The objective of this study was to analyze the volatile compounds in rice under various milling degrees using a mass spectrometry-based electronic nose and discriminant function analysis (DFA). Less volatile components were more frequently found in rice with a lower milling degree. Milling degree resulted in a shift of DF1 to the left side of the DFA plot. This indicated that the DF1 scores were correlated with the milling degree of rice. Brown rice was found to have more volatile components regardless of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Moreover, the use of brown rice for analysis of volatile compounds, mainly 2-acetyl-1-pyrroline (2-AP), minimizing the labor and time required for sample preparation would improve the efficiency analysis of progeny in an aromatic rice breeding program (Bryant, McClung, & Grimm, 2011). Besides of that, Han, Dong, and Noh (2016) demonstrated that brown rice exhibits a greater amount of volatile constituents compared to polished rice, regardless of milling degree.…”
mentioning
confidence: 99%
“…Moreover, the use of brown rice for analysis of volatile compounds, mainly 2-acetyl-1-pyrroline (2-AP), minimizing the labor and time required for sample preparation would improve the efficiency analysis of progeny in an aromatic rice breeding program (Bryant, McClung, & Grimm, 2011). Besides of that, Han, Dong, and Noh (2016) demonstrated that brown rice exhibits a greater amount of volatile constituents compared to polished rice, regardless of milling degree.…”
mentioning
confidence: 99%